Visuospatial Working Memory Tasks May Not Reduce the Intensity or Distress of Intrusive Memories - Badawi, Amalia; Steel, Zachary; Berle, David (Frontiers in Psychiatry, 2022)
Cognitive interventions involving visuospatial tasks, such as the game “Tetris” have demonstrated efficacy in reducing the frequency of intrusive memories. However, it remains unclear whether these tasks also reduce the perceived intensity and distress of these memories. We investigated whether either of two visuospatial tasks: a Tetris intervention or Digital Corsi task, following the viewing of an analogue trauma (film) resulted in decreased intensity and distress for intrusive memories over the following week, when compared to a control condition. Participants (n=110) were randomly assigned to task conditions after viewing the film. Linear mixed models indicated no between-group differences for reductions in intensity or distress over the course of the week. These findings highlight an important boundary to the benefits of such visuospatial tasks, in that while they may be associated with reductions in intrusion memory frequency, individuals may nonetheless continue to experience distress when intrusions do occur.